Desenvolvimento de um questionário para identificar os fatores que interferem no cumprimento da Política Nacional de Saúde Bucal, no campo da Atenção Básica: elaboração de itens e validação de conteúdo - Bruno Rafael Teixeira Balen (2017)
When performing health policies, evaluation allows identifying problematic situations and their causes. This study described the development and validity of the questionnaire content to assess the National Policy of Oral Health (NPOH) performance from the point of view of dental surgeons in Primary Care. In this paper, comprehensiveness presents itself as a transversal and integrating principle to the formulation of health policies. To evaluate the NPOH, the access/patient welcoming and attending, infrastructure, work process, participative management and institutional support, social participation were defined as assessment dimensions.The stages for defining the questionnaire items were: delimitation of the theoretical model, survey about the reality regarding oral health services in Primary Care (focal groups with dental surgeons and managers) and content validation by experts (research professors, managers and dental surgeons) concerning the questionnaire qualitative evaluation about repetition, items clarity and ambiguity and editing suggestions. It was necessary to have three rounds of content validation resulting in 38 items with a satisfactory comprehension level, and therefore the questionnaire final version was valid to evaluate the performance of NPOH.